Intrinsic non-radiative voltage losses in fullerene-based organic solar cells - Benduhn, J; Tvingstedt, K; Piersimoni, F; Tropiano, M; Riede, M (Springer Nature, 2017)
Organic solar cells demonstrate external quantum efficiencies and fill factors approaching those of conventional photovoltaic technologies. However, as compared with the optical gap of the absorber materials, their open-circuit voltage is much lower, largely due to the presence of significant non-radiative recombination. Here, we study a large data set of published and new material combinations and find that non-radiative voltage losses decrease with increasing charge-transfer-state energies. This observation is explained by considering non-radiative charge-transfer-state decay as electron transfer in the Marcus inverted regime, being facilitated by a common skeletal molecular vibrational mode. Our results suggest an intrinsic link between non-radiative voltage losses and electron-vibration coupling, indicating that these losses are unavoidable. Accordingly, the theoretical upper limit for the power conversion efficiency of single-junction organic solar cells would be reduced to about 25.5% and the optimal optical gap increases to 1.45–1.65 eV, that is, 0.2–0.3 eV higher than for technologies with minimized non-radiative voltage losses.